AEROBIC EXERCISE TRAINING DURING ADOLESCENCE REVERSES THE METABOLIC DYSFUNCTION INDUCED BY THE LITTLE REDUCTION MODEL (Arquivos do Mudi, 2023)
Sedentary lifestyle and consumption of high-calorie foods contribute to the development ofindividuals with risk factors for non-communicable diseases. Aerobic exercise is one of themain non-pharmacological strategies in this confrontation. This work aims to evaluate theeffects of moderate-intensity exercise (MIE) on biometric and metabolic parameters of adultmale Wistar rats, programmed for obesity during the lactation period. The litters werestandardized in 9 pups until the 3rd day of life, and later adjusted in Normal Litters (NL), andReduced Litters (SL). At 21 days, the offspring were weaned and divided into sedentary(SED) and exercised (EXE) groups, forming 4 experimental groups: NL-SED, NL-EXE, SL-SED and SL-EXE. EXE rats performed a moderate-intensity treadmill running protocol from30 to 60 years old. All groups were euthanized at 120 days. The results showed that the litterreduction made the animals heavier (p<0.0001), hyperphagic (p<0.001), greater mesenteric fatstock (p<0.0001), insulin resistant (p=0.0001) and glucose intolerant (p=0.0001), whencompared to equivalent controls. MIE promoted a reduction in body weight (p=0.001) andmesenteric fat (p<0.0001), better insulin sensitivity (p=0.01) and glucose tolerance (p=0.003).It is concluded, therefore, that MIE performed in adolescence attenuates the deleteriouseffects observed on body composition and glucose metabolism in adult animals, programmedearly for obesity.